2020
DOI: 10.1080/13816810.2020.1766087
|View full text |Cite
|
Sign up to set email alerts
|

KCNV2 retinopathy: clinical features, molecular genetics and directions for future therapy

Abstract: KCNV2-associated retinopathy or "cone dystrophy with supernormal rod responses" is an autosomal recessive cone-rod dystrophy with pathognomonic ERG findings. This gene encodes Kv8.2, a voltagegated potassium channel subunit that acts as a modulator by shifting the activation range of the K + channels in photoreceptor inner segments. Currently, no treatment is available for the condition. However, there is a lack of prospective long-term data in large molecularly confirmed cohorts, which is a prerequisite for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 66 publications
0
37
0
Order By: Relevance
“…The current study reported a further 28 novel KCNV2 variants—a significant addition to the 95 previously reported variants. 9 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The current study reported a further 28 novel KCNV2 variants—a significant addition to the 95 previously reported variants. 9 …”
Section: Discussionmentioning
confidence: 99%
“…The current study reported a further 28 novel KCNV2 variants which is a significant addition to the 95 previously reported variants. 9 With the recognition of the pathognomonic ERG phenotype, targeted KCNV2 screening is of high yield as previously suggested. 17 In the same study KCNV2retinopathy was identified as the second most common cause (11.3%) of paediatric inherited retinal disease (IRD) in an Emirati cohort of 71 patients.…”
Section: Genetics and Disease Epidemiologymentioning
confidence: 94%
See 1 more Smart Citation
“…Progressive COD/CORD are characterised by cone photoreceptor degeneration, which may be followed by subsequent rod photoreceptor loss. These disorders typically present with progressive loss of central vision, colour vision disturbance and photophobia ( 11 , 44 ). We discuss their retinal imaging, focusing on five of the most common genotypes: GUCA1A , GUCY2D , ABCA4 , PRPH2 and RPGR .…”
Section: Cone and Cone-rod Dystrophiesmentioning
confidence: 99%
“…Some patients present with color vision deficits, myopia, central scotoma, and, particularly in younger patients, nystagmus. Fundus findings are usually unremarkable in children, but adults frequently exhibit distinct macular changes or retinal pigment epithelial (RPE) atrophy (2)(3)(4)(5)(6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%